Additive manufactured high entropy alloys: A review of the microstructure and properties. (August 2022) - Zhang, Wei; Chabok, Ali; Kooi, Bart J.; Pei, Yutao
Graphical abstract: Highlights: Critical overview on recent progresses of additive manufactured high entropy alloys (HEAs). Selective laser melting, laser melting deposition, electron beam melting and recently emerging wire arc additive manufacturing are comparatively studied. The microstructure characteristics and mechanical properties of additive manufactured HEAs are comprehensively summarized. Emerging functional properties of additive manufactured HEAs are discussed. The future prospects of HEAs fabricated by additive manufacturing are presented. Abstract: High entropy alloys (HEAs) are promising multi-component alloys with unique combination of novel microstructures and excellent properties. However, there are still certain limitations in the fabrication of HEAs by conventional methods. Additive manufactured HEAs exhibit optimized microstructures and improved properties, and there is a significantly increasing trend on the application of additive manufacturing (AM) techniques in producing HEAs in recent years. This review summarizes the additive manufactured HEAs in terms of microstructure characteristics, mechanical and some functional properties reported so far, and provides readers with a fundamental understanding of this research field. We first briefly review the application of AM methods and the applied HEAs systems, then the microstructure including the relative density, residual stress, grain structure, texture and dislocation networks, element distribution, precipitations and the influence of post-treatment on the microstructural evolution, next the mechanical properties consisting of hardness, tensile properties, compressive properties, cryogenic and high-temperature properties, fatigue properties, creep behavior, post-treatment effect and the strengthening mechanisms analysis. Thereafter, emerging functional properties of additive manufactured HEAs, namely the corrosion resistance, oxidation behaviors, magnetic properties as well as hydrogen storage properties are discussed, respectively. Finally, the current challenges and future work are proposed based on the current research status of this topic.